STRATEGI PENGEMBANGAN EKOWISATA BAHARI DI KABUPATEN SUMBAWA (Studi Pada Obyek Wisata Pantai Prajak Kabupaten Sumbawa) - S Suprianto; Tedy Sukriadinata Saputra (Pusat Riset dan Publikasi, 2023)
This study aims to analyze the strategy for developing marine ecotourism in Sumbawa Regency. This research is a descriptive research conducted to examine the strategy for developing marine ecotourism at the Prajak Beach tourism object, Sumbawa Regency. The type of data used is qualitative data in the form of interviews with research informants obtained directly from the original source. Data analysis in this study used the SWOT analysis technique to formulate various alternative strategies in developing marine ecotourism at the Prajak Beach tourist attraction, Sumbawa Regency. This analysis is based on logic that can maximize strengths and opportunities, but simultaneously minimize weaknesses and threats. The results of this study indicate that the SWOT analysis in developing marine ecotourism at the Prajak Beach tourism object in Sumbawa Regency produces four alternative strategies, namely SO strategy, WO strategy, ST strategy and WT strategy. The resulting alternative development strategy is to maintain and develop the potential of marine ecosystems found in marine ecotourism at Prajak Beach through water or sea conservation education, adding facilities and infrastructure to support tourism, participating in various training programs to improve the quality of managing human resources, optimizing utilization of various information media to introduce tourism objects to the public, increase public awareness in protecting marine ecosystems to prevent illegal fishing or other actions that can damage marine ecosystems.